A Stimuli‐Responsive Macromolecular Gear: Interlocking Dynamic Helical Polymers with Foldamers. (23rd March 2020) - Rodríguez, Rafael; Suárez‐Picado, Esteban; Quiñoá, Emilio; Riguera, Ricardo; Freire, Félix
Abstract: Herein, macromolecular gears composed of helical poly(phenylacetylenes) (PPAs) bearing short oligopeptides as pendant groups are described, in which the two structural motifs (framework and substituents) are combined. These gears are obtained by polymerization of the acetylene groups introduced at the C‐terminus of short oligopeptides formed by achiral (Aib) n units ( n =1–3) derivatized at the N‐terminus by a single enantiomer ( R or S ) of α‐methoxy‐α‐trifluoromethylphenylacetic acid (MTPA, Mosher's reagent). The chiral information of the MTPA is transmitted to the achiral Aib fragments and, through either chiral tele‐induction and/or chiral harvesting mechanisms, is further transferred to the polyene backbones, which adopt preferentially P or M helical senses. Moreover, these materials also show dynamic behavior and respond to the action of external stimuli by either inverting the P / M sense and/or modifying the elongation in fully reversible processes. Abstract : Macromolecular gear : Long‐range chiral induction is produced in poly(phenylacetylene)s (PPAs) that bear achiral Aib oligomers capped at the N‐termini with a chiral acid (Mosher's reagent). The chiral residue induces screw sense preferences in the different Aib oligomers, which are harvested by the PPAs adopting an excess of a single‐handed helical structure.